Evaluation of total flavonoid contents of Mariami Iranian date fruits (Phoenix dactylifera L.) using different extracts - Ibrahim, H Sani; Mohd Adzim Khalili, Rohin; U, Abdulkareem (2015)
Introduction: Phoenix dactylifera Linn., a date palm is known for its nutritional and numerous health benefits due to its presence of bioactive compounds. Iranian Mariami date fruit (IMDF) is widely found and used by people around the globe. Purpose: This study was aimed to determine the total flavonoid contents (TFCs) presence in IMDFs of the three different extracts (methanolic extract, hydro-ethanolic extract, and aqueous). Materials and Methods: All the samples were extracted from three different solvents and measured using aluminum chloride colorimetric method, with some modification. Result: The TFCs of the extracts in decreasing order was methanolic extract (11 mg quercetin [QE]/g) > hydro-ethanolic extract (7.1 mg QE/g) > aqueous (6.8 mg QE/g), respectively. Conclusion: The antioxidant potential effect of IMDFs was due to its high TFCs, which can be benefited to human body systems. In this study, methanol solvent shown to have a high affinity of extracting the flavonoid contents.